Yanks Over Europe : American Flyers in World War II - Klinkowitz, Jerome (Book collections on Project MUSE., 2015)
Contrasts between fighter combat and the bombers' war support Klinkowitz's belief that notions of the air war were determined by one's position in it. He extends his thesis by showing the vastly different style of air war described by veterans of the North African and Mediterranean campaigns and concludes by studying the effects of such combat on adversaries and victims. Air combat, Klinkowitz writes, offers a unique perspective on the nature of war. The experience of combat has inspired authors to combine exquisite descriptions with probing thoughtfulness, covering the full range of human expr.